Testing the Limits: Forbidden Love in Two Anglophone Caribbean Texts - Buxton, Camille Alexander (Academic Quarter | Akademisk kvarter, 2011)
Testing the Limits: Forbidden Love in Two Anglophone Caribbean Texts by Camille Alexander Buxton is initiated by the discussion whether forbidden love, a form of romantic love that is a recurrent theme in literature, is constructed or natural. In the article the theme is addressed as a characteristic of natural, human emotions rather than a social construct with a specific code of conduct, indicative of Western culture. Forbidden love is a theme in some Caribbean texts, and in the article, Buxton examines texts from two Trinidadian authors, Shani Mootoo’s (2005) He Drown She in the Sea and Elizabeth Nunez’s (2006) Prospero’s Daughter.